Delivery Mode On Myopic Women (Literature Review) - Ratna Dwi Jayanti; Noor Syafaatin Udhma; Euvanggelia Dwilda Ferdinandus; Ivon Diah Wittiarika; Nurul Azizah (Rifa'Institute, 2022)
Hormonal changes and hemodynamic changes in pregnancy cause an increase in blood volume and water retention which causes a thickening of the cornea of ??the eye and affects blood flow in the eye. This condition is thought to trigger temporary myopia or worsen myopia that occurred before pregnancy. This will have an impact on the choice of delivery method because pushing in the second stage of labor can increase the risk of retinal detachment. The aim of the study was to determine the method of delivery in patients with myopia, using a meta-analysis. The results showed that obstetrics and gynecology specialists, as well as ophthalmologists, recommended instrumental delivery or cesarean section for women with myopia citing concerns that vaginal delivery would increase the risk of detachment. In addition, the impact of labor on the ocular system was found to be not so significant. While the method of delivery in women with myopia, it was found that most of the vaginal deliveries were spot-on.